Pengukuran Capability Level menggunakan Monitor, Evaluate and Assess (MEA) COBIT 5 - Paul Rio Pelupessy; Nivaan, Goldy Valendria; Tomasila, Golda; Reynaldi Siwalette; Wattimena, Virginia Evelin (Yayasan Literasi Sains Indonesia, 2025)
The application of information technology as a support for the processes and activities of a business organization or company is very necessary, including in a government institution. Moreover, in its utilization, technology must also run in conjunction with proper information management and administration to support the sustainability of organizational activities in the future. How optimal the performance and the evaluation of human resources in the management process of technology that has not been carried out is also a consideration as the basis for this research. Therefore, the objective of this research is to measure the maturity level of the existing information technology to analyze at which level the organization stands, so that suggestions can be made for the use of IT in the organization to align with the goals and fulfill the vision and mission of organization XYZ. This measurement uses the Monitor, Evaluate and Assess (MEA01) domain and the result obtained is that the organization is at level 3. Therefore, it is expected that from the results of this research, the organization can implement proposed improvements to IT governance for the advancement of the agency in the future.